On Lipschitz ball noncollapsing functions and uniform co-Lipschitz mappings of the plane - Olga Maleva (Abstract and Applied Analysis)
We give a sharp estimate on the cardinality of point preimages of a uniform co-Lipschitz mapping on the plane. We also give a necessary and sufficient condition for a ball noncollapsing Lipschitz function to have a point with infinite preimage.